Developing general view of quality models for e-learning from developers perspective - Abdellatief, Majdi; Md Sultan, Abu Bakar; Jabar, Marzanah A.; Abdullah, Rusli (2010)
The growth of the Internet and web as a source of information and communication has led companies to use websites as an education tool.E-learning is gaining more acceptance as days pass because it provides learning opportunity any time and in any place. Moreover, e-learning has the potential to benefit learner/student, instructor, manager, administrator, organization and society in many ways.Thus it is important to evaluate e-learning from these various perspectives. The main aim of this work is to propose new technique to evaluate e-learning website quality from developer’s view.Our technique adopts the weights of quality characteristics which are obtained by carefully selected questionnaires’ from professional developer. We also present the evaluation process using AHP technique and the result of trial evaluation for validation of our technique. As result, we believe that proposed technique will be useful to effective evaluation, as well as to develop system with high quality. Furthermore, this technique would enhance the relationship between instructors and developers.